(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Human rights are the rights inherent to all human beings regardless of race, sex, ethnicity, language religion or any other status. Human rights include right to life and liberty, freedom from slavery and torture, freedom of opinion and expression right to work and education and many other such rights. These rights lay down positive and negative duties on states, i.e duty to do certain acts and to refrain from certain acts. General perception about human rights is that they deal only violent acts such as terrorism, torture, repression etc. No doubt these acts constitute violation of human rights, but unfair economic structure, and resultant inequalities also form the content of human rights. The Universal Declaration of Human Rights, 1948 in Article 25, proclaimed the right of every human being to a standard of living adequate to health and well being of himself and of his family including food, clothing, housing, medical care and necessary social services. However, there is a dismal record behind implementation of Article 25 at universal level. Acording to world bank indicators in 2016 about 750 million people around the world life in extreme poverty i.e below 1.90 per day. According to Unicef report arond 46% of those living in extreme poverty are children.